Development and Implementation of the MPPT Based on Incremental Conductance for Voltage and Frequency Control in Single-Stage DC-AC Converters - Javier Alonso Ramírez Torres; Orlando Lastres Danguillecourt; Roberto Adrián González Domínguez; Guillermo Rogelio Ibáñez Duharte; Laura Elena Verea Valladares; Joel Pantoja Enríquez; Jesús Antonio Enríquez Santiago; Andrés López López; Antonio Verde Añorve (Energies)
This paper presents the design, simulation, and experimental evaluation of a low-cost, fixed-step MPPT algorithm based on the incremental conductance technique for operation in a low-power photovoltaic (PV) system with a full-bridge DC-AC converter. The performance of the MPPT algorithm was improved by selecting an appropriate fixed perturbation step size and frequency, ensuring efficient power tracking. The implementation was further optimized by restructuring the conventional algorithm and adapting the DC-AC converter control parameters, which enhanced overall performance and optimized coupling for AC loads. The simulation was performed in Simulink/Matlab with a 560 Wp PV system and a resistive load, under variable irradiation conditions. The perturbation step size was set to 1%, and the perturbation frequency ranged between 2 Hz and 15 Hz, with the converter output at 60 Hz. Experimentally, it was validated at an irradiance of 1000 W/m2 and an ambient temperature of 45 °C. The algorithm achieved simulation efficiencies of up to 98.93% and an average experimental efficiency of 96.76%. The response time improved by 86% with a perturbation frequency of 15 Hz. This developed MPPT algorithm demonstrates its reliability, accuracy, and feasibility for implementation.